Identification of a methyl-accepting chemotaxis protein for the ribose and galactose chemoreceptors of Escherichia coli. - Kondoh, H (1979)
The ribose and galactose chemoreceptors of Escherichia coli have previously been identified as the ribose- and galactose-binding proteins. We now report the discovery of a methyl-accepting chemotaxis protein that functions in the transfer of receptor signals from these two binding proteins to the flagella. This protein is distinct from previously described methyl-accepting chemotaxis proteins. Its level of methylation is influenced by D-ribose, D-galactose, and certain structural analogues of them. This methyl-accepting protein is required for chemotaxis toward those attractants; mutants in the trg gene, which do not methylate this protein, are devoid of taxis toward D-ribose, D-galactose, and their analogues. In addition, methylation of the methyl-accepting protein in response to each of these attractants requires the appropriate binding protein. The binding protein's chemoreceptor function is required for such methylation, but its transport activity is not. Because the function of this methyl-accepting chemotaxis protein involves two of the best-characterized chemoreceptors, the discovery of this protein represents a promising base for further study of the linkage between chemoreceptors and flagella in bacteria.